2010
DOI: 10.1002/hep.23640
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Macrophages Suppress Viral Replication and Prevent Severe Immunopathology in an Interferon-I-Dependent Manner in Mice

Abstract: The innate immune response plays an essential role in the prevention of early viral dissemination. We used the lymphocytic choriomeningitis virus model system to analyze the role of tissue macrophages/Kupffer cells in this process. Our findings demonstrated that Kupffer cells are essential for the efficient capture of infectious virus and for preventing viral replication. The latter process involved activation of Kupffer cells by interferon (IFN)-I and prevented viral spread to neighboring hepatocytes. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 40 publications
4
85
1
Order By: Relevance
“…Previous studies showed an accumulation of LCMV particles in the liver within minutes after an intravenous challenge (37). In line with this, we observed a reproducible LCMV replication in the liver of mice inoculated 24 h earlier, reaching average titers of 2.27 ϫ 10 5 PFU/g of liver.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Previous studies showed an accumulation of LCMV particles in the liver within minutes after an intravenous challenge (37). In line with this, we observed a reproducible LCMV replication in the liver of mice inoculated 24 h earlier, reaching average titers of 2.27 ϫ 10 5 PFU/g of liver.…”
Section: Resultssupporting
confidence: 90%
“…Previous data from our group and others have shown that Kupffer cells from healthy mice are specialized phagocytes with only marginal cytokine production ex vivo under steady-state conditions (31) and that Kupffer cells are among the first to be infected with LCMV, thereby limiting viral spread (37)(38)(39). We studied here in detail the endocytic ability of F4/80 highKupffer cells and inflammatory monocytes during early LCMV infection.…”
Section: Resultsmentioning
confidence: 98%
“…Splenectomy did not affect serum HBsAg levels compared with the sham-operated group (Figure 4), a result that is consistent with previous studies showing that splenectomized mice exhibited normal viral clearance during lymphocytic choriomeningitis virus infection. 24 From these findings, we hypothesize that the liverdraining LNs can provide a functional substitute for the spleen in the induction of immune response, but that the spleen still primes an anti-HBV immune response when present during infection. This interpretation is supported by the observation of an anti-HBV specific immune response in the spleen in this mouse model (data unpublished).…”
Section: Induction Of Anti-hbv Responses In the Liver-draining Lnsmentioning
confidence: 87%
“…In many models of liver injury, hepatic macrophages themselves are involved in the pathogenesis of the liver damage (31). In other models, macrophages play a role in preventing severe hepatic immunopathology (32) or in limiting the severity of liver immunopathology (33). These particular mechanisms do not appear to play a significant role in our HBV model, as mice lacking macrophages or CXCL13/CXCR5 did not have a significant difference in liver injury, despite developing significantly different immune responses to HBV (Figures 3, 5, and 6).…”
Section: Discussionmentioning
confidence: 99%